2013
DOI: 10.1556/jfc-d-12-00019
|View full text |Cite
|
Sign up to set email alerts
|

Continuous In Situ Electrogeneration of o-Benzoquinone in Microreactor: Application to High Yield Reaction with Benzenethiols

Abstract: We have successfully demonstrated that a microflow reactor is extremely useful in controlling reactions involving an unstable o-benzoquinone. As a model reaction, Michael addition reaction between o-benzoquinone generated from electrochemical oxidation of catechol and benzenethiols was employed. This reaction system enables selective oxidation of catechol avoiding the oxidation of benzenethiol, although these oxidation potentials are close to each other. The examination of several reaction conditions indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This is probably due to the accumulation of a thin lm of the product 6, 7 or 8 at the surface of the WE electrode and therefore, the WE electrode performance is inhibited to a certain extent. [37][38][39][40] All the voltammetric data demonstrated that there were no new redox peaks (i.e., in addition to the original peaks of pure catechol) aer adding a nucleophile to catechol under applied experimental conditions. On the one hand, the absence of new redox peaks suggests that no stable intermediates were formed during the electrochemical oxidation of compound 1 in the presence of compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the accumulation of a thin lm of the product 6, 7 or 8 at the surface of the WE electrode and therefore, the WE electrode performance is inhibited to a certain extent. [37][38][39][40] All the voltammetric data demonstrated that there were no new redox peaks (i.e., in addition to the original peaks of pure catechol) aer adding a nucleophile to catechol under applied experimental conditions. On the one hand, the absence of new redox peaks suggests that no stable intermediates were formed during the electrochemical oxidation of compound 1 in the presence of compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, much research has been reported on the use of anodic oxidation, such as the Shono oxidation, 273–275 carbon–carbon cross-coupling reactions, 276,277 oxidation of 5-HMF to 2,5-furandicarboxylic acid, 278 cascade electrogeneration and transformation of unstable intermediates, 279–281 paired electrosynthesis 282,283 and domino-oxidation–reductions. 284,285 In general, different types of electrochemical reactions can be summarized as: (1) direct electrochemical reaction with solvent degradation as counter reaction, (2) direct electrochemical reaction with nonsolvent degradation as counter reaction, (3) mediated or catalyzed electrochemical reaction, (4) redox combined electrochemical reaction (Fig.…”
Section: Oxidation Reactions In Flow Electrochemistrymentioning
confidence: 99%
“…We conceived that the flow microreactor system could efficiently oxidize catechol 26 to generate o ‐benzoquinone 27 , which could immediately react with nucleophiles downstream. As a proof‐of‐concept, the reaction of o ‐benzoquinone with 4‐isopropylbenzenethiol 28 was selected, with the formation of the diaryl thioether motif 29 expected (Figure 9a) [53,54] …”
Section: Electrogenerated Active Species and Its Flash Use For Reactionsmentioning
confidence: 99%